Renal replacement therapy in the ICU: comparison of clinical features and outcomes of patients with acute kidney injury and dialysis-dependent end-stage renal disease - KARAKURT, SAİT; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2015)
The goal of this study is to study clinical features and outcomes of the patients who had renal replacement therapy (RRT) in the intensive care unit (ICU) between 2000 and 2007. We retrospectively studied 222 patients. Overall ICU mortality and invasive mechanical ventilation (IMV) rates were 58.1 and 61.3 %. The mean APACHE II score was 27.6 +/- A 8.3. Chronic dialysis (CD) patients formed 45.5 % of the study population. Acute kidney injury (AKI) patients had higher rates of IMV (73 vs. 51.5 %, p = 0.002), cancer (27.8 vs. 7.9 %, p a parts per thousand currency sign 0.001) and mortality (67.8 vs. 50.5 %, p = 0.010) than CD patients. AKI patients with normal kidney function (NKF) before ICU admission had poorer prognosis than acute-on-chronic kidney disease (CKD) and CD patients (78.6, 51 and 50.5 %, respectively, p a parts per thousand currency sign 0.001). Multivariate analysis showed that IMV (OR, 14.8; 95 % CI, 5.47-40.05; p a parts per thousand currency sign 0.001) and having NKF before hospitalization (OR, 2.8; 95 % CI, 1.04-7.37; p = 0.041) were predictors of overall ICU mortality. Additionally, IMV is found as a prognostic factor for both AKI (OR, 18.7; 95 % CI, 4.48-77.72; p a parts per thousand currency sign 0.001) and CD patients (OR, 8.14; 95 % CI, 2.01-33.04; p = 0.003), but APACHE II score is meaningful only for CD patients (OR, 1.13; 95 % CI, 1.02-1.26; p = 0.024). The areas under the ROC curves for APACHE II score were 0.52 (95 % CI, 0.39-0.66) for AKI and 0.78 (95 % CI, 0.55-0.89) for CD patients. The observed ICU mortality among patients requiring RRT is high and IMV is associated with mortality. AKI patients have increased mortality compared to CD patients. AKI patients with past NKF have poorer prognosis than acute-on-CKD and CD patients.
Keywords: Acute kidney injury; End-stage kidney disease; Intensive care unit; Renal replacement therapy; INTENSIVE-CARE-UNIT; CRITICALLY-ILL PATIENTS; HOSPITAL MORTALITY; FAILURE; IMPACT; CANCER; DYSFUNCTION